Belajar dari Sejarah Maritim Mandar (1900-1980): Mulai dari Terbentuknya Jaringan hingga Keberadaan Pelabuhan Kembar - Mahamid, Mochammad Nginwanun Likullil (Universitas Hamzanwadi, 2024)
This article aimed to review a book that explained maritime affairs entitled Jaringan Maritim Mandar: Studi tentang Pelabuhan “Kembar” Pambauwang dan Majene di Selat Makassar 1900-1980 written by Abd. Rahman Hamid in 2021. The book, an important contribution to national historiography, discussed maritime history and networks in Indonesia. In the Mandar case study, it had two “twin” ports, namely Pambauwang and Majene. This was based on the author's experience working in the maritime field from 2010 to 2020. However, the book, originally the author’s dissertation in the History Program at the University of Indonesia and was compiled two years ago, was still deemed necessary for review to provide an assessment of the book and other matters related to the structure of the writing. This book review article was written using the descriptive-analytic method, which began with an explanation of the background of the book’s writing, a review of previous works, the sources used, and the systematics of the book. Then, an analysis was carried out with various other sources in the form of books, journals, and final assignments, which had the same material. Other important aspects included the relationship between chapters, the advantages and disadvantages of books, and their academic benefits.